Dose escalation pre-clinical trial of novel DOK7-AAV in mouse model of DOK7 congenital myasthenia - Cossins, J; Kozma, I; Canzonetta, C; Hawkins, A; Beeson, D; Sepulveda, P; Dong, YY (Oxford University Press, 2025)
Congenital myasthenic syndromes are a group of inherited disorders characterized by defective neuromuscular transmission and fatigable muscle weakness. Causative mutations have been identified in over 30 genes, including DOK7, a gene encoding a post-synaptic protein crucial in the formation and stabilization of the neuromuscular junction. Mutations in this gene are one of the leading three most prevalent causes of congenital myasthenia in diverse populations across the globe. The majority of DOK7 congenital myasthenic patients experience varying degrees of disability despite receiving optimized treatment (usually salbutamol), necessitating the development of improved therapeutic approaches. Here, we executed a dose escalation pre-clinical trial using a DOK7 congenital myasthenic syndrome mouse model to assess the efficacy of AMP-101, an innovative recombinant adeno-associated viral gene replacement therapy. This mouse model harbours a duplication in the Dok7 gene that corresponds to the mutation most commonly found in DOK7 congenital myasthenia patients, c.1124-1127dupTGCC. The model has a much more severe phenotype than patients, and lives for only a few days. AMP-101 is based on AAVrh74 and contains human DOK7 cDNA under the control of a muscle-restricted promoter. Three doses of AMP-101 (2 × 1013 vg/kg, 6 × 1013 vg/kg or 1 × 1014 vg/kg) were administered intraperitoneally at 4 days of age. We show that the two higher doses of 6 × 1013 vg/kg and 1 × 1014 vg/kg generated enlarged neuromuscular junctions and rescued the very severe phenotype of the model. Treated mice became at least as strong as wild-type littermates, as demonstrated by using an inverted screen hang test, a rotarod test and a grip strength test. EMG showed that the treated model mice had decrement of compound muscle action potential on repetitive nerve stimulation, which indicates defective signalling at the neuromuscular junction. However, male models treated with 1 × 1014 vg/kg showed the least decrement that was not statistically different from wild-type littermates. Western blot analysis demonstrated robust expression of DOK7 in the diaphragm and tibialis anterior muscles. These data show that AMP-101 is an effective treatment in a mouse model for DOK7 congenital myasthenia, and suggests that AMP-101 is a promising candidate to move forward to clinic trials as a gene therapy for patients.